2022
DOI: 10.1016/j.ebiom.2021.103767
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel-driven bioelectric signalling regulates metastasis in triple-negative breast cancer

Abstract: Summary Background There is a critical need to better understand the mechanisms that drive local cell invasion and metastasis to develop new therapeutics targeting metastatic disease. Bioelectricity is an important mediator of cellular processes and changes in the resting membrane potential (RMP) are associated with increased cancer cell invasion. However, whether the RMP can be used to target invading cancer cells is unknown. Methods We employed both genet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 86 publications
(113 reference statements)
0
22
0
Order By: Relevance
“…In addition, the researchers found that Kv1.3 channel blockade was able to lead to phosphorylation of the transcription factor CREB in LUAD A549 cells and play a specific role in cell proliferation, apoptosis and differentiation, thereby affecting the development of lung cancer(LC) cells ( 15 ). Kv1.5 overexpression driving resting membrane potential(RMP) hyperpolarization may alter adhesion and morphology of triple-negative breast cancer(TNBC) cells and increase TNBC cell migration and invasion ( 16 ).…”
Section: Relationship Between Potassium Channel and Tumormentioning
confidence: 99%
“…In addition, the researchers found that Kv1.3 channel blockade was able to lead to phosphorylation of the transcription factor CREB in LUAD A549 cells and play a specific role in cell proliferation, apoptosis and differentiation, thereby affecting the development of lung cancer(LC) cells ( 15 ). Kv1.5 overexpression driving resting membrane potential(RMP) hyperpolarization may alter adhesion and morphology of triple-negative breast cancer(TNBC) cells and increase TNBC cell migration and invasion ( 16 ).…”
Section: Relationship Between Potassium Channel and Tumormentioning
confidence: 99%
“…The K + channel EAG has been found to be expressed in 100% of cervical cancer biopsies analyzed and overexpression of EAG in human cells has been shown to increase cell proliferation in culture ( 71 , 72 ). Furthermore, overexpressing K + channels in breast cancer cells has been found to drive cell migration mediated by cadherin-11 and MAPK signaling ( 73 ). Calcium-dependent K + channel K Ca 3.1 also promoted proliferation by directly interacting with ERK1/2 and JNK signaling pathways ( 74 ).…”
Section: Bioelectricity In Cancer Processesmentioning
confidence: 99%
“…Te metal ions released after the degradation are observed to have some signifcant ramifcations, such as excess calcium caused by Ca 2+ ions released from CaO 2 which is thought to cause mitochondrial damage [166,178,179]. Te released Ba 2+ ions produced by the degradation reaction of BaO 2 are known to act as a potassium ion pump suppressor, inhibiting tumor progression [180,181].…”
Section: Targeting Metal Ion Homeostasismentioning
confidence: 99%